Optimizing main cutting force in high-pressure jet-assisted turning using Taguchi method - Kramar, Davorin; Sekulić, Milenko; Rodić, Dragan; Pejić, Vlastimir (Journal of Production Engineering, 2024)
In high pressure turning, the optimization of cutting forces is crucial to improve the efficiency and precision of machining. In this study, the Taguchi method is used to systematically investigate and optimize the input parameters that influence the cutting forces. By using an orthogonal array and analyzing the signal-to-noise ratio, the main factors affecting the cutting force are identified and their optimal values are determined. The effectiveness of the optimization is confirmed by validation tests, which show a significant improvement in cutting performance. The results provide actionable insights for machining and lead to better decision-making and process control in high-pressure turning. This research not only highlights the benefits of the Taguchi method in process optimization, but also contributes to advancing machining techniques by minimizing cutting forces and improving overall process stability.